Penerapan Strategi Project Based Learning (PJBL) untuk Meningkatkan Literasi Numerasi Siswa pada Pembelajaran Matematika di SDN Dana Bura - Eka Safriani; Syarifuddin Syarifuddin; Syahru Ramadhan (Pepatudzu : Media Pendidikan dan Sosial Kemasyarakatan, 2026)
This study aims to describe the implementation of the Project-Based Learning (PBL) strategy in improving students' numeracy literacy in mathematics at SDN Dana Bura, as well as to measure the progress in numeracy skills among fourth-grade students following this strategy's application. The method used is Classroom Action Research (CAR) based on the Kemmis & McTaggart model, conducted over two cycles. The research subjects include 14 fourth-grade students at SDN Dana Bura, Ambalawi District, Bima Regency, West Nusa Tenggara. Data collection methods involve observation, numeracy literacy tests (pre-test and post-test), questionnaires, interviews, and documentation. Quantitative data were analyzed by calculating the average scores and the percentage of learning completion, while qualitative data were analyzed through data reduction, presentation, and conclusion. The results indicate that the consistent application of the PjBL strategy effectively enhanced students' numeracy literacy. The class average increased from 51.43 (pre-cycle) to 66.79 (Cycle I) and 82.14 (Cycle II). The percentage of learning completion rose from 21.43% to 57.14% (Cycle I) and 85.71% (Cycle II), surpassing the success indicator of 75%. The quality of learning implementation also improved from 75.00% (Good) to 93.75% (Excellent). Therefore, the use of the PjBL strategy has proven effective in enhancing students' numeracy literacy through contextual and meaningful mathematics learning.